CAPACITY ANALYSIS OF SELECTED MAJOR INTERSECTIONS ON THE ROUTE AUTOBUS TERA-KALITY BUS STATIONS AND MITIGATION MEASURES - Kebede, Abel; Tilahun, Tamru (Zede Journal of Ethiopian Engineers and Architects, 2023)
Engineering mitigation measures were proposed in order to improve the existing levels of service for major intersections. The adjustment to the existing cycle time, delineation of movements on existing lane configuration and geometric modifications to observe the improvements on the respective levels of service were among the proposed mitigation measures. It was hypothetically believed that there exist short comings on the route Autobus Tera - Kality bus stations from congestion and level of service points of view. Subsequently, four signalized intersections were selected based on statistical outputs of mixed type of questionnaire. They were then analyzed by using software tool (SIDRA) so that the outcome could be used as a source of information and data for transport sector organizations and academic reference. Accordingly, the level of service of Eliana hotel site improved from level F to D & the average delay from 167.3 seconds to 54.7 seconds and level of service of Immigration site improved from level F to E & the average delay from 435.5 seconds to 68.7 seconds. Moreover, level of service for both Harambae and Saris Adey Ababa sites improved from F to D & the average delay from 642.6 seconds to 54.2 seconds and from 865.1 seconds and 49.13 seconds, respectively. Key words: level of service, delay, major intersections, SIDRA